Hubungan Persepsi dan Karakteristik Sosial Ekonomi Budaya Masyarakat dalam Pengembangan Ekowisata Bahari di Pulau Nusmapi - Selvi Tebay; Yuanike Kaber; Elsha Prangin Angin; Emmanuel Manangkalangi; Agnestesya Manuputty; Mina Regina Rumayomi (Jurnal Sumberdaya Akuatik Indopasifik, 2021)
Marine tourism is a type of special interest tourism, namely by managing and utilizing marine and coastal landscapes, both those that are managed directly such as swimming, boating, snorkeling, diving, or indirectly such as picnics and beach sports. Nusmapi Island has the potential to be developed as a marine tourism object which has the potential for waters and coral reefs that are in good condition. The purpose of this study was to determine the relationship between the level of public perception and the socio-economic conditions of the local community on Nusmapi Island. In October-November 2020 this research was carried out on Nusmapi Island, Manokwari Regency. The descriptive exploratory method is by conducting a survey to the research location. The data collected were analyzed descriptively by tabulating and displayed in the form of pictures, tables, and graphs to provide an explanation of the information obtained in this study. The relationship between the level of perception and socio-economic and cultural aspects of society was analyzed by multiple regression. The variables of age, gender, education, main occupation, and additional work were positively correlated with community perception, while length of stay and ethnic origin were negatively correlated with perceived level. The correlation value between the 7 independent variables (X1-X7) and the dependent variable (Y) is 0.839 which is included in the very strong category. The value of the coefficient of determination 61% explains the variables in the resulting regression model, the remaining 39% is influenced by other factors outside the model. Age is a significant social variable on people's perceptions of the development of marine tourism on Nusmapi Island. The community as the main component in development has an important role in developing local potential that comes from nature, socio-culture or improving the community's economy through the development of marine tourism.